2017
DOI: 10.1002/2016jd025572
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Noah land surface model with various runoff parameterizations over a Tibetan river

Abstract: Runoff parameterizations currently adopted by the (i) Noah‐MP model, (ii) Community Land Model (CLM), and (iii) CLM with variable infiltration capacity hydrology (CLM‐VIC) are incorporated into the structure of Noah land surface model, and the impact of these parameterizations on the runoff simulations is investigated for a Tibetan river. Four numerical experiments are conducted with the default Noah and three aforementioned runoff parameterizations. Each experiment is forced with the same set of atmospheric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 57 publications
3
39
3
2
Order By: Relevance
“…The NSE values range from 0.70 to 0.89 at Yellow River stations, which are better than previous works where NSE values range from 0.49 to 0.85 based on GLDAS1/Variable Infiltration Capacity simulations (Cuo et al, 2013) and 0.31 to 0.89 based on GLDAS1/Noah simulations (Zheng et al, 2017). Bai et al (2016) also evaluated streamflow simulations of GLDAS1 over the TP, and their results showed that Kling-Gupta efficiency values vary from À0.75 to 0.09 at the TNH and ZMD stations, which are much lower than those from CSSPv2 simulations (Table 1).…”
Section: Journal Of Advances In Modeling Earth Systemscontrasting
confidence: 62%
See 1 more Smart Citation
“…The NSE values range from 0.70 to 0.89 at Yellow River stations, which are better than previous works where NSE values range from 0.49 to 0.85 based on GLDAS1/Variable Infiltration Capacity simulations (Cuo et al, 2013) and 0.31 to 0.89 based on GLDAS1/Noah simulations (Zheng et al, 2017). Bai et al (2016) also evaluated streamflow simulations of GLDAS1 over the TP, and their results showed that Kling-Gupta efficiency values vary from À0.75 to 0.09 at the TNH and ZMD stations, which are much lower than those from CSSPv2 simulations (Table 1).…”
Section: Journal Of Advances In Modeling Earth Systemscontrasting
confidence: 62%
“…For runoff generation, Zheng et al () compared four different schemes over upper Yellow River in the TP and found soil water storage‐based runoff parameterizations outperformed water table‐based runoff schemes for the seasonally frozen and high‐altitude rivers. Thus, we incorporated the Variable Infiltration Capacity (Liang et al, ) runoff parameterization into CSSP following Oleson et al ().…”
Section: Model Data and Experimental Designmentioning
confidence: 99%
“…precipitation for the period 1979-2013. CMFD has been widely employed for land surface modeling over China (Chen et al, 2011;Leng et al, 2015;Liu & Xie, 2013;Xue et al, 2013;Zheng et al, 2017).…”
Section: Model Input and Setupmentioning
confidence: 99%
“…A six-year-long (2009-2014) experiment was created using version 3.6.1 of the WRF model [42] and the WRFDA data assimilation [43][44][45]. The experiment was started on 1 January 2009; however, that year was used only as a spin-up for the soil system in the model, and it is not included in this paper as is typically done in other literature [46,47]. The WRF model was nested inside ERA-Interim [48].…”
Section: Wrf Simulationmentioning
confidence: 99%